SISTEM RESERVASI LAPANGAN OLAHRAGA BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) (STUDI KASUS: KAWALI SPORT CENTER) - Ariya Handika Mulyana; Rian Dwi Cahya Supriatman; Tuti Rohayati (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
The reservation process at Kawali Sport Center is still carried out manually, causing booking delays, schedule conflicts, and slow payment verification, while users cannot check court availability in real time. This study aims to design and develop a web-based reservation system using the Rapid Application Development (RAD) method. The system was built with PHP and MySQL, designed with Figma and UML, and tested using Black Box Testing, while integrating Midtrans for online payments. The results show that the system accelerates booking, minimizes schedule conflicts, and simplifies payment verification. The RAD method also ensures faster and more flexible development, improving service quality at Kawali Sport Center and providing a reference for similar sports facility management systems.